Effect of Corrosion Attack on Pall Ring in Hydrocarbon Industry - Elias, Nur Farhana; Azzura Ismail (Research Progress in Mechanical and Manufacturing Engineering, 2026)
This study investigates effect of corrosion attack on pall ring in hydrocarbon industry.Pall ring are widely used in hydracarbon industry for liquid contact in distillation, absorpation and chemical reactions.This research involved testing surface morpohlogy and elements analysis (Scanning Electron Microsopy and energy Dispray X-Ray),electrochemical testing and mechanical testing (tensile and hardness). A sodium chloride (3.5% NaCl) was used as the electrolyte due to its similarity to the ionic composition of seawater.SEM analysis showed there have corrosion in pall ring in three yearprocess.Electrochemical test showed corrosion rate in the presenceused 3.5% NaCL and mechanical properties show the impact materialstrength or hardness. The findings of this research, offer a comprehensive understanding of how prolonged industrial use influences the integrity, durability, and functional reliability of Pall rings in demanding operational settings.